An approach to predicting based on monitoring data by means of combined situational-inductive modeling (the main idea and expected results) - Stefanyshyn, D.V. (Математичне моделювання в економіці, 2019)
This approach is proposed to use to predict the behavior of complicated technogenous, ecological and economic systems based on regular monitoring data forming time series by means of simplified models of regression type. The approach uses the idea of decomposition of complex modeling and prediction tasks by means of regression models based on monitoring data to overcome the excessive structural and parametric uncertainty of real dynamic systems. Цей підхід пропонується використовувати для прогнозування поведінки складних природних, техногенних, екологічних та економічних систем на основі регулярних моніторингових даних, що формують часові ряди, за допомогою спрощених моделей регресійного типу. У підході використовується ідея декомпозиції складних завдань моделювання та прогнозування за допомогою регресійних моделей на основі даних моніторингу для подолання надмірної структурної та параметричної невизначеності реальних динамічних систем.